The method of scattered electron spectrum division into resonance and quasielastic parts in the energy region of giant resonances - Denyak, V.V.; Khvastunov, V.M.; Paschuk, S.A.; Schelin, H.R. (Вопросы атомной науки и техники, 2005)
The pioneer method for extraction of quasielastic part from the spectrum of scattered electrons is proposed. The
essence of the method is in simultaneous multipole analysis of the mix of quasielastic and resonant formfactors. The
identification of resonant peaks and quasielastic part of the formfactor have been held not in scattered electron
spectra but in the transition probability energy dependence of each multipolarity where there difference between
resonant and quasielastic processes is clear. The pure quasielastic spectrum for ⁶⁵Cu with the electron energy
E₀ =225 MeV and scattered angle θ=65° was obtained as a result of the application of this method. Предложен новый метод для извлечения квазиупругой (КУ) части из спектра рассеянных электронов. Сущность метода заключается в одновременном мультипольном анализе смеси КУ и резонансного сечения. Идентификация резонансных пиков и КУ части сечения проводится не в спектрах рассеянных электронов, а в энергетической зависимости приведенной вероятности каждой мультипольности, где имеющееся различие между резонансным и КУ процессами проявляется более ясно. Чистый КУ спектр для ядра ⁶⁵Cu при начальной энергии электронов Е₀ = 225 МэВ и угле рассеяния θ = 65° получен как результат применения этого метода. Запропоновано новий метод для витягу квазіпружної (КП) частини зі спектра розсіяних електронів. Сутність методу полягає в одночасному мультипольному аналізі суміші КП і резонансного переріза. Ідентифікація резонансних піків і КП частини переріза проводиться не в спектрах розсіяних електронів, а в енергетичній залежності приведеної імовірності кожної мультипольності, де наявне розходження між резонансним і КП процесами виявляється більш ясно. Чистий КП спектр для ядра ⁶⁵Cu при початковій енергії електронів Е₀ = 225 МеВ і куті розсіювання θ = 65° отримано як результат застосування цього методу.